Knowledge management in distributed software development: a systematic review - Tamy Ishii, Fernanda (2013)
Software development is characterized as a knowledge intensive activity. Particularly, Distributed Software Development (DSD) is an approach that demands more attention for coordination and communication among members of distributed team, due to regional, cultural and infrastructure differences. Knowledge has being, increasingly, seen as the most important strategic resource in organizations. So, the management of this knowledge is critical to organizational success. Knowledge Management (KM) is a set of processes directed at creating, capturing, storing, sharing, apply, and reuse of knowledge, which are useful to decision making. The purpose of this paper is to present a systematic review carried out to identify the processes, techniques, methods, practices and/or tools adopted for Knowledge Management in Distributed Software Development. With this systematic review some interesting points for research were identified.